Convergence of ethernet PON and IEEE 802.16 broadband access networks and its QoS-aware dynamic bandwidth allocation scheme - Kun Yang; Shumao Ou; Guild, K.; Hsiao-Hwa Chen (IEEE journal on selected areas in communications, 2009)
IEEE 802.16 and Ethernet Passive Optical Network (EPON) are two promising broadband access technologies for high-capacity wireless access networks and wired access networks, respectively. They each can be deployed to facilitate connection between the end users and the Internet but each of them suffers from some drawbacks if operating separately. To combine the bandwidth advantage of optical networks with the mobility feature of wireless communications, we propose a convergence of EPON and 802.16 networks in this paper. First, this paper starts with presenting the converged network architecture and especially the concept of virtual ONU-BS (VOB). Then, it identifies some unique research issues in this converged network. Second, the paper investigates a dynamic bandwidth allocation (DBA) scheme and its closely associated research issues. This DBA scheme takes into consideration the specific features of the converged network to enable a smooth data transmission across optical and wireless networks, and an end-to-end differentiated service to user traffics of diverse QoS (Quality of Service) requirements. This QoS-aware DBA scheme supports bandwidth fairness at the VOB level and class-of-service fairness at the 802.16 subscriber station level. The simulation results show that the proposed DBA scheme operates effectively and efficiently in terms of network throughput, average/maximum delay, resource utilization, service differentiation, etc.